Synthesis and characterization of condensed Schiff bases and their iron salts with aldamine - Meng, Chao; Gu, Zheng; Wang, Jianfa; Sui, Jinyong; Hu, Shaokai; Zhang, Susu; Zhang, Xiaoyi; Li, Peiyao; Liu, Wenjin; Hu, Yifan (Polimery, 2023)
As a result of the coordination polycondensation of p-phenylenediamine with glyoxal or terephthalaldehyde, two types of long-chain conjugated Schiff bases differing in structure were obtained. Their ferric salts were also obtained. Elemental analysis and infrared spectroscopy (FTIR) were used to evaluate the chemical structure of the obtained Schiff bases and their salts. Thermal stability (TGA) and electrical conductivity were also investigated.